Ptychographic X-ray computed tomography of extended colloidal networks in food emulsions. (January 2016) - Nielsen, Mikkel Schou; Munk, Merete Bøgelund; Diaz, Ana; Pedersen, Emil Bøje Lind; Holler, Mirko; Bruns, Stefan; Risbo, Jens; Mortensen, Kell; Feidenhans'l, Robert
Abstract : Graphical abstract: Abstract : Highlights: The 3D microstructure of an oil-in-water food emulsion is obtained using ptychographic X-ray computed tomography. A spacial resolution of approximately 300 nm was obtained with good image contrast. The food emulsion displays an extended network of fat globules connecting >98% of total lipid volume. Through image analysis the colloidal network was found to consist of partially coalesced fat globules. Abstract: As a main structural level in colloidal food materials, extended colloidal networks are important for texture and rheology. By obtaining the 3D microstructure of the network, macroscopic mechanical properties of the material can be inferred. However, this approach is hampered by the lack of suitable non-destructive 3D imaging techniques with submicron resolution. We present results of quantitative ptychographic X-ray computed tomography applied to a palm kernel oil based oil-in-water emulsion. The measurements were carried out at ambient pressure and temperature. The 3D structure of the extended colloidal network of fat globules was obtained with a resolution of around 300 nm. Through image analysis of the network structure, the fat globule size distribution was computed and compared to previous findings. In further support, the reconstructed electron density values were within 4% of reference values.